ANALISIS KESIAPAN SUMBER DAYA IAIN TERHADAP PERUBAHAN STATUS MENJADI UIN SYEKH NURJATI CIREBON - Kartimi, Kartimi; Mulyani, Asep (Holistik: Journal for Islamic Social Sciences, 2016)
The aims of this research to analisys toward IAIN to be UIN Syekh Nurjati Cirebon, analysis readiness IAIN Syekh Nurjati Cirebon to support changes become UIN Cirebon, analysis constraints becomes UIN Syekh Nurjati Cirebon. This research conducted in IAIN Cirebon. The subject of this research is IAIN stakeholder consist of leaderships, 33 lectures, 17 staff administration, and 350 student of institute, and user around Cirebon. This research is qualitative research type case study. Instrument of this research using questionnaire, guidance interview, and documentation. Data Analysis using three type, consist of data reduction, data presentation, and data verificated by induktif, deduktif, and comparative. The result show refers to regulation of ministry of religion number 15, 2015 about changing higher education in ministry of religion about changing IAIN become UIN, consist of number of student of university, qualified of lecturer and staff education, and acreditation of department. Resources unmet are number of qualified lecturer, facilitaties and infrastuctures, number of department and faculty, and curriculum of integration. Stakeholder provided positive respon and support to changing IAIN become UIN Syekh Nurjati Cirebon. IAIN Syekh Nurjati Cirebon have a number of problem consist of facilitaties and infrastuctures incomplete, the number of lecture suitably qualified, the number of department and faculty, curriculum doesn’t standarized, academic atmosphere doesn’t condusive, SOP is still print out book but not implemented, UIN development team unform.            Keyword: Resources, Readiness, IAIN, UIN